1991
DOI: 10.2307/3236174
|View full text |Cite
|
Sign up to set email alerts
|

Multiple species effects and spatial autocorrelation in detecting species associations

Abstract: Abstract. The traditional approach to the analysis of species association within a community, based upon co‐occurrence in sampling units such as quadrats, has been to test all pairs of species, using a 2 × 2 contingency table for each pair. It has long been recognised that all these tests are not independent of each other, but there is an additional problem in that the association between any particular pair may depend on the combination of the other species that are present or on the environmental factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…the spatial autocorrelation issue (Dale et al 1991;Jongman et al 1997;Schiegg 2003). In order for two relevés not to be overly influenced by each other's seeds and clonal plants, 100 m was taken as the minimum distance between two relevés during the field research, with that distance being much greater in the majority of cases.…”
Section: Methodsmentioning
confidence: 99%
“…the spatial autocorrelation issue (Dale et al 1991;Jongman et al 1997;Schiegg 2003). In order for two relevés not to be overly influenced by each other's seeds and clonal plants, 100 m was taken as the minimum distance between two relevés during the field research, with that distance being much greater in the majority of cases.…”
Section: Methodsmentioning
confidence: 99%
“…By deflating the magnitude of the test statistic by the appropriate amount, depending on the degree of nonrandomness in the data, an estimate of the significance of the test statistic in the presence of autocorrelation is obtained. A limitation of Tavaré and Altham's (1983) method is that it is valid only when the within-species spatial patterns meet Markovian assumptions (Dale et al 1991). Dale et al (1991) extended Tavaré and Altham's (1983) approach and suggested a Monte Carlo procedure that can be applied to the analysis of multispecies 2 k contingency tables, where k is the number of species.…”
Section: Adjustment Methodsmentioning
confidence: 99%
“…A limitation of Tavaré and Altham's (1983) method is that it is valid only when the within-species spatial patterns meet Markovian assumptions (Dale et al 1991). Dale et al (1991) extended Tavaré and Altham's (1983) approach and suggested a Monte Carlo procedure that can be applied to the analysis of multispecies 2 k contingency tables, where k is the number of species. Their method involves defining a null model which includes information on the spatial patterns of each species.…”
Section: Adjustment Methodsmentioning
confidence: 99%
See 2 more Smart Citations